REVIEW OF BEHAVIORISM THEORY ON NGENGER WAY OF LIFE AMONG SANTRI - Ishomudin, Muhammad; Haryanto, Budi; Astutik, Anita Puji (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This study aims to analyze the way of life of ngenger among santri (pesantren students) from a behavioristic point of view at Fadllillah Waru Sidoarjo Islamic Boarding School. This study applies a phenomenological qualitative approach. The object of this study is the students who ngenger in the pesantren (Islamic boarding schools, in some conditions, may be closer to an Islamic Monastery). Data were collected by observation and interview techniques. Data analysis using interactive model analysis techniques from Miles and Huberman. The results of the study explained that students who "ngenger" have their own goals, such as learning tasawuf, recompense, devotion, making blessings, to life expectancy. They also have their duties such as cleaning ndalem, washing, and ironing kyai (pesantren principal) and bu nyai (the wife of pesantren principal) clothes, preparing kyai and bu nyai food, accompanying kyai and bu nyai wherever they go. Ngenger can shape student behavior, including obedient, obedient, patient, resigned, responsible, simple, humble, gentle behavior, and ability to interpret life. The more obedient a student is to the kyai, the better and more nimble he will be in completing his duties. In ngenger, it can be known that John B Watson's behaviorism theory of stimulus-response can influence a person's behavior.